Analisis System Usability Scale (SUS) dan Perancangan Sistem Self Service Pemesanan Menu di Restoran Berbasis Web - Anak Agung Ngurah Hary Susila; Dewa Made Sri Arsa (Universitas Komputer Indonesia, 2023)
COVID-19 is a global pandemic with 220 countries infected with this virus and 55,326,907 confirmed cases. In Indonesia, from March to November 2021, there were 478,720 positive cases, where these cases were identified from clusters of offices, factories, educational establishments, hospitals/health centers, and finally a new cluster was found in a restaurant. The Ministry of Tourism and Creative Economy has issued guidelines for preventing COVID-19 in restaurants by providing menu lists and ordering food or drinks based online. The purpose of the study was to design an architectural model for the application of self service menus and orders at restaurants. The method used for designing this system is the Waterfall method with the System Usability Scale (SUS) method for testing application usability. The results of the research are the self-service architectural model of the menu and order application, there are two user actors, namely visitors and restaurant admins. The self service menu and order application architecture model has a menu page that can be accessed by guests and admins, namely the main system page, food and beverage menu, order check out page, admin order page and to access the system you can use a QR Code. The results of the application usability test using the System Usability Scale (SUS) method get an average value of 70 or the Good category (good). Key Words: Architecture Models, COVID-19, Restaurant, Self Service Application, System Usability Scale